Լռութեան մասին - Վազրիկ Բազիլ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Молчание — захватывающее явление, о котором можно много говорить и даже разглагольствовать. Синоним молчания — покой, тишина, безмолвие, перерыв и бессловесность. Однако молчание — не отсутствие голоса, а нарушение ожидания слова. Если какой-то человек ожидает от другого слова, но это слово отсутствует, то этот человек молчит не из-за отсутствия слова, а из-за того, что не удовлетворяет ожидания. Таким образом, ни «спящий», ни «покойный» не молчат, потому что никто от них не ожидает разговоров. Молчание, как и уединение, являются общими явлениями — относительными и коммуникационными. Молчание не переламывает общение, а продолжает его другим способом. Здесь также проявляется основное упоминание молчания — молчание всегда «говорящее». Silence is an attracting phenomenon that can be talked about a lot and even chattered away. Synonyms of silence are peace, dumbness, pause and speechlessness. Silence, however, is not the lack of voice, but the suppression of the expectation of words. If a person expects words from another person, and he/she lacks them, then it means that the person is silent, not because there is a lack of words, but because the expectation is not met. Thus, neither the “dormant” nor the “deceased” is silent, because no one expects them to speak. Silence, as well as solitude are social phenomena, i.e. they are relative and communicative. Silence does not break the communication, but continues it in another way. And here appears the main paradox — silence is always “speaking.”
Keywords: Հայոց եկեղեցի; Կրոնագիտություն; Փիլիսոփայություն